2004
DOI: 10.1124/jpet.103.061747
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Selective Allosteric Modulator Potentiates the Activity of Native Metabotropic Glutamate Receptor Subtype 5 in Rat Forebrain

Abstract: We found that N- {4-chloro-2-[(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)methyl]phenyl}-2-hydroxybenzamide (CPPHA), is a potent and selective positive allosteric modulator of the metabotropic glutamate receptor subtype 5 (mGluR5). CPPHA alone had no agonist activity and acted as a selective positive allosteric modulator of human and rat mGluR5. CPPHA potentiated threshold responses to glutamate in fluorometric Ca 2ϩ assays 7-to 8-fold with EC 50 values in the 400 to 800 nM range, and at 10 M shifted mGluR5 agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
170
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(179 citation statements)
references
References 28 publications
9
170
0
Order By: Relevance
“…Interestingly, unlike other mGlu 5 PAMs characterized to date, CPPHA appears to elicit receptor activation through a novel allosteric site that does not appear to directly involve the MPEP site. 17,26,43,44 Radioligand tools, either as negative allosteric modulators (NAMs), PAMs, or silent allosteric modulators (SAMs), are currently unavailable for the CPPHA site, and the potential impact of an appropriate in vivo tool compound from the CPPHA series is still lacking and thus leaves an important remaining question regarding potential in vivo efficacy for PAMs which modulate their activity outside the MPEP site. Interestingly, examination of DFB and CPPHA in independent signaling mechanisms (ERK1/2 phosphorylation and calcium mobilization) demonstrated that differential PAM signaling is possible, supporting the notion that PAMs which engage distinct allosteric binding sites and presumably unique modulator-receptor conformations can differentially facilitate downstream signaling responses.…”
Section: Schizophrenia and First Generation Mglu 5 Pamsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, unlike other mGlu 5 PAMs characterized to date, CPPHA appears to elicit receptor activation through a novel allosteric site that does not appear to directly involve the MPEP site. 17,26,43,44 Radioligand tools, either as negative allosteric modulators (NAMs), PAMs, or silent allosteric modulators (SAMs), are currently unavailable for the CPPHA site, and the potential impact of an appropriate in vivo tool compound from the CPPHA series is still lacking and thus leaves an important remaining question regarding potential in vivo efficacy for PAMs which modulate their activity outside the MPEP site. Interestingly, examination of DFB and CPPHA in independent signaling mechanisms (ERK1/2 phosphorylation and calcium mobilization) demonstrated that differential PAM signaling is possible, supporting the notion that PAMs which engage distinct allosteric binding sites and presumably unique modulator-receptor conformations can differentially facilitate downstream signaling responses.…”
Section: Schizophrenia and First Generation Mglu 5 Pamsmentioning
confidence: 99%
“…42 Following DFB, N-[5-chloro-2-[(1,3-dioxoisoindolin-2-yl)methyl]phenyl]-2-hydroxybenzamide (CPPHA, 4) was disclosed as a much more potent mGlu 5 PAM. 17 The CPPHA benzamide series of PAMs was characterized as having a shallow structureÀactivity relationship (SAR), poor physicochemical properties, and limited activity at the rat mGlu 5 receptor and was therefore not utilized in vivo. Interestingly, unlike other mGlu 5 PAMs characterized to date, CPPHA appears to elicit receptor activation through a novel allosteric site that does not appear to directly involve the MPEP site.…”
Section: Schizophrenia and First Generation Mglu 5 Pamsmentioning
confidence: 99%
See 1 more Smart Citation
“…mGluR5 receptors regulate the activation of glutamate NMDA receptors acting as an enhancer of NMDA-activated currents and increased phosphorylation of the receptor through intracellular signalling MAPK/ERK and calcium responsive element binding (O'Brien et al 2004;Liu et al 2007) via a Src-family tyrosine kinase (Kotecha et al 2003).…”
Section: Neurobiology Of Mglur5mentioning
confidence: 99%
“…The worsening of the detrimental effects of NMDA receptor antagonists by mGlu5 receptor antagonist suggests that activation of mGlu5 receptors may represent a plausible approach for ameliorating symptoms of schizophrenia (Marino and Conn 2002;Moghaddam 2004). Recent behavioral studies using 3-cyano-N-(1,3-diphenyl-1H-pyrazol-5-yl)benzamide (CDPPB), a positive allosteric modulator of the mGlu5 receptor (Kinney et al 2005b;O'Brien et al 2004), show that pretreatment with this compound reverses amphetamine-induced hyperlocomotion and prepulse inhibition deficit, two tests which serve to model some aspects of schizophrenia in rodents (Kinney et al 2005a). …”
mentioning
confidence: 99%